ANALISIS PERAN BANK SAMPAH HAPAKAT HATANTIRING DESA LUWUK KANAN SEBAGAI BENTUK PARTISIPASI MASYARAKAT DALAM PENGELOLAAN - Dea Imut; Nova Riyanti (Jurnal Ilmu Sosial dan Ilmu Politik)
Waste banks are waste handling places available in Indonesia to help deal with common problems that occur due to waste. In this activity, the more people from Luwuk Kanan village participate, the more waste management at the Hapakat Hatantiring waste bank can develop. The aim of this research is to analyzethe role of the Hapakat Hatantiring waste bank in Luwuk Kanan village as a form of community participation in waste management. This research uses descriptive qualitative research methods. Data collection through Observation,Iinterviews, Documentation. From the research results, it is known that commonity participation is still lacking, this can be seen from the fact that only a few people who are classified as elderly and school children partisipate in managing waste at the Hapakat Hatantiring waste bank Luwuk Kanan village. This is due to a lack of education from the waste bank to the community about the importanceof participating in waste management. The Hapakat Hatanting waste bank can collect approximately 20-30 Kg of waste in 1 week. However this activity is still not optimal because it is limited by implementation time which is only carriedout once a week. The Hapakat Hatantiring waste bank’s suggestion is to increase its operational hours two to three times a week so that the role of the waste bank can be more optimal and the waste bank management can educate the public about the importance of  participating in waste bank management.